Critical Care Admission of an HIV Patient with Diabetic Ketoacidosis Secondary to Pembrolizumab. (25th March 2020) - Cuenca, John A.; Laserna, Andres; Reyes, María P.; Nates, Joseph L.; Botz, Gregory H.
Abstract : Background . Pembrolizumab is a checkpoint inhibitor that targets the programmed cell death-1 receptor (PD-1) and has shown to be effective against several malignancies, including lung cancer. However, life-threatening immune-related adverse events can result from these immunotherapy treatments. Case presentation . A 62-year-old man with HIV, metastatic adenocarcinoma of the lung, and no previous history of diabetes presented to the emergency department with new-onset nausea, vomiting, and generalized weakness. Glucose was 1191 mg/dl, hemoglobin A1c 11%, and potassium 6.9 mEq/L. He had metabolic acidosis with a lactate of 6.6 mmol/L and anion gap of 38 mEq/L, and ketones were detected on the urinalysis. Severe diabetic ketoacidosis was diagnosed, and the patient was admitted to the intensive care unit. Additional investigations showed low C-peptide and negative anti-glutamic acid decarboxylase antibody, anti-insulin antibody, and anti-islet-antigen 2Ab antibody. After ruling out other possible etiologies, pembrolizumab was considered to be the cause of the diabetes and ketoacidosis. Conclusions . Life-threatening adverse drug events associated with checkpoint inhibitors such as pembrolizumab are on the rise. We recommend to closely follow and monitor patients receiving these immunotherapies. This strategy could lead to early detection and prevention, as well as reduction of more serious life-threatening complications requiring intensive care.